"Could we have predicted this?" The association of a future mental health need in young people with a non‐specific complaint and frequent emergency department visits. Issue 5 (7th October 2021) - Fang, Andrea; Hersh, Melissa; Birgisson, Natalia; Saynina, Olga; Wang, Nancy E
Abstract: Objective: Mental health emergencies among young people are increasing. There is growing pressure for emergency departments to screen patients for mental health needs even when it is not their chief complaint. We hypothesized that young people with an initial non‐specific condition and emergency department (ED) revisits have increased mental health needs. Methods: Retrospective, observational study of the California Office of Statewide Health Planning and Development Emergency Department Discharge Dataset (2010–2014) of young people (11–24 years) with an index visit for International Classification of Diseases, Ninth Revision diagnostic codes of "Symptoms, signs, and ill‐defined conditions" (Non‐Specific); "Diseases of the respiratory system" (Respiratory) and "Unintentional injury" (Trauma) who were discharged from a California ED. Patients were excluded if they had a prior mental health visit, chronic disease, or were pregnant. ED visit frequency was counted over 12 months. Regression models were created to analyze characteristics associated with a mental health visit. Results: Patients in the Non‐Specific category compared to the Respiratory category had 1.2 times the odds of a future mental health visit (OR 1.20; 95% CI 1.17–1.24). Patients with ≥1 ED revisit, regardless of diagnostic category, had 1.3 times the odds of a future mental health visit. Patients with both a Non‐Specific index visit and 1, 2, and 3 or more revisits with non‐specific diagnoses had increasing odds of a mental health visit (OR 1.38; 95% CI 1.29–1.47; OR 1.70; 95% CI 1.46–1.98; OR 2.20; 95% CI 1.70–2.87, respectively.) Conclusions: Young people who go to the ED for non‐specific conditions and revisits may benefit from targeted ED mental health screening.